Ground reaction forces during steeplechase hurdling and waterjumps - Kipp, S.; Taboga, P.; Kram, R. (Sports Biomechanics, 2017)
Athletes in the 3,000 m steeplechase track and field event negotiate unmovable hurdles and waterjumps. Ground reaction forces (GRF) in the steeplechase were quantified to elucidate injury risks / mechanisms and to inform coaches. Five male and five female steeplechasers participated. GRF were measured during treadmill running, and using specially mounted force platforms, during hurdle and waterjump takeoffs and landings at 5.54 m/s (males) or 5.00 m/s (females). Results are presented as: male mean ± SD / female mean ± SD. Initial and active peaks of vertical GRF during treadmill running were 2.04 ± 0.72 / 2.25 ± 0.28 BW and 3.11 ± 0.27 / 2.98 ± 0.24 BW. Compared to treadmill running, peak vertical forces were greater (p < 0.001) for: hurdle takeoff (initial: 4.25 ± 0.86 / 3.78 ± 0.60 BW, active: 3.82 ± 0.20 / 3.74 ± 0.32 BW), hurdle landing (active: 4.41 ± 1.13 / 4.21 ± 0.21 BW), waterjump takeoff (initial: 4.32 ± 0.67 / 4.56 ± 0.54 BW, active: 4.00 ± 0.24 / 3.83 ± 0.31 BW), and waterjump landing (initial: 3.45 ± 0.34 / #3.78 ± 0.32 BW, active:5.40 ± 0.78 / #6.23 ± 0.74 BW); (#) indicates not statistically compared (n = 2). Based on horizontal impulse, athletes decelerated during takeoff steps and accelerated during landing steps of both hurdling and waterjumps. Vertical GRF peaks and video indicated rearfoot strikes on the treadmill but midfoot strikes during hurdle and waterjump landings. Potentially injurious GRF occur during the steeplechase, particularly during waterjump landings (up to 7.0 BW). ABSTRACT FROM AUTHOR